Reproductive Coercion, Intimate Partner Violence, and Unintended Pregnancy Among Latina Women. Issue 3 (February 2022) - Grace, Karen Trister; Decker, Michele R.; Alexander, Kamila A.; Campbell, Jacquelyn; Miller, Elizabeth; Perrin, Nancy; Glass, Nancy
Reproductive coercion (RC) describes a range of behaviors that restrict reproductive autonomy including pregnancy coercion, birth control sabotage, and controlling the outcome of a pregnancy. RC is associated with pregnancies that are mistimed and unwanted (i.e., unintended). Past research demonstrates that Latina women have higher risk for RC and for unintended pregnancy. This cross-sectional descriptive study with Latina women ( n = 482) examined prevalence and risk factors for RC, evaluated the association of RC and unintended pregnancy among women with a past-year pregnancy, and explored use of safety and harm reduction strategies. A tablet survey was administered to women attending a community health center, between the ages of 15 and 45, who self-identified as Latina and who had a dating or sexual partner in the past year. Approximately one in six (16.8%) experienced past-year RC and risk factors included younger age (adjusted odds ratio [AOR] = 0.95, 95% confidence interval [CI] = [0.91, 1.00], p = .038) and concurrent intimate partner violence (IPV; AOR = 4.47, 95% CI = [2.06, 9.70], p < .001). IPV questions were specific to the partner involved with RC behaviors. For the 185 participants who reported a past-year pregnancy, RC was associated with lower pregnancy planning scores (β = –.27, 95% CI = [–0.41, –0.13], p < .001). The combination of experiencing RC and IPV appeared particularly potent in lowering pregnancy planning scores (β = –.15, 95% CI = [–0.29, 0.00], p = .052). Approximately 10.6% of participants engaged in harm reduction strategies, most commonly ending an unhealthy or abusive relationship (6.1%) and using less detectable methods of contraception so that partners would not find out (3.4%). The study articulates the risk of RC and its intersection with IPV and unintended pregnancy for Latina women. Providers working with racially and ethnically marginalized women have an important role in promoting safety and harm reduction strategies that include offering less detectable methods of contraception and support in leaving unhealthy and abusive relationships.